Digital maps of mechanical geotechnical parameters using GIS. Issue 1 (1st January 2020) - Aldefae, Asad H.; Mohammed, Jareer; Saleem, Hiba D.
Abstract: Geographical Information System (GIS) is a powerful tool for representing huge data and producing an actual visualization of subsurface information and parameters in the form of 3D scenes that can be used by the geotechnical engineers in the design of footing and foundation. This paper focuses on producing digital geotechnical maps for the main geotechnical parameters that can be used in the preliminary design stage. Considerable data of 164 borehole logs presenting a 17, 000 km 2 (i.e. Wasit province, south of Baghdad, Iraq) are collected, analyzed, tabulated in an excel sheet, and used as input data to create the digital maps. The studied parameters are bearing capacity, shear strength, coefficient of consolidation, compressibility parameters, and groundwater levels. The results show that the GIS technique is a great tool to visualize the geotechnical parameters that can be easily used directly in the assessment of the site investigation reports and even in the foundation design. The digital values of the bearing capacities, shear strength, and compressibility parameters are clearly visualized and accurately replicate the soil layers of the study area. However, other geotechnical parameters are needed to further consider it in more digital maps.